Pola Pendidikan Karakter Pada Anak Autis di SLB Islam Qothrunnada - Nur Sakinah Ali; Ahmad Muhammad Diponegoro (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2023)
This study examines the role of character education in autistic children at SLB Islam Qothrunnada. Autism is a neurobiological disorder that affects social interaction, communication, and individual behavior patterns. Character education plays a crucial role in shaping positive attitudes and values in autistic children. This research employs a qualitative approach through field research involving teachers at Qothrunnada Islamic Special School as informant interviews. The interview instrument was utilized to gather data on the behavior model of character education for autistic children, the positive values instilled, and the obstacles encountered in the character education process. The study's findings reveal that the character education model for autistic children at Qothrunnada Islamic Special School is implemented through habituation in daily life, encompassing the school, the surrounding environment, and the home. Character education in autistic children is implemented through the promotion of positive values that align with the specific needs and challenges faced by these children. The establishment of character education patterns is crucial to ensure the harmonious collaboration between teachers, parents, and individuals within the child's immediate environment.Â Keywords: Character Education, Autism, Habituation, Model.